Simple anthropometrics are more correlated with health variables than are estimates of body composition in Yup'ik people. - Bray, Maria; Pomeroy, Jeremy; Knowler, William C; Bersamin, Andrea; Hopkins, Scarlett; Brage, Søren; Stanhope, Kimber; Havel, Peter J; Boyer, Bert B (Obesity, 2013)
To (1) evaluate the relationships between several indices of obesity with obesity-related risk factors; (2) compare the accuracy of body composition estimates derived from anthropometry and bioimpedance analysis (BIA) to estimates of body composition assessed by doubly-labeled water (DLW); and (3) establish equations for estimating fat mass (FM), fat-free mass (FFM), and percent body fat (PBF) in Yup'ik people.Participants included 1,056 adult Yup'ik people from 11 communities in Southwestern Alaska. In a sub-study of 30 participants, we developed population-specific linear regression models for estimating FM, FFM, and PBF from anthropometrics, age, sex, and BIA against criterion measures derived from total body water assessed with DLW. These models were then used with the population cohort and we analyzed the relationships between obesity indices and several health-related and disease status variables: (1) fasting plasma lipids, (2) glucose, (3) HbA1c, (4) adiponectin, (5) blood pressure, (6) diabetes (DM), and (7) cerebrocoronary vascular disease (CCVD) which includes stroke and heart disease.The best model for estimating FM in the sub-study used only three variables-sex, waist circumference (WC), and hip circumference and had multiple R(2) = 0.9730. FFM and PBF were calculated from FM and body weight.WC and other anthropometrics were more highly correlated with a number of obesity-related risk factors than were direct estimates of body composition. Body composition in Yup'ik people can be accurately estimated from simple anthropometrics.